THE FUNGAL COMMUNITIES ON SPRING WHEAT SEEDS FROM DIFFERENT ENVIRONMENTAL CONDITIONS - Wiewióra, Barbara; Mańkowski, Dariusz (Plant Breeding and Seed Science, 2018)
Seeds of ten cultivars of spring wheat from five different localized breeding stations were tested for seed health. The same seeds were sown in Radzików in field experiment and its seed health after harvest was evaluated also. The basic material of wheat was infected by numerous fungi: 36 fungal species belonging to 24 genera and the most often occurred: Alternaria alternata, Epicoccum purpurascens, Fusarium spp., Drechslera spp. and B. sorokiniana. It was found significant differences between cultivars for total fungi occurred on seeds, for seed infection by main pathogens (B. sorokiniana, Drechslera spp. and Fusarium spp.). Also seeds from breeders were strongly infected by these pathogens in comparison to seeds harvested in field experiment in Radzików.